FAKTOR - FAKTOR PENYEBAB KETERLAMBATAN PELAKSANAAN PEKERJAANPROYEK KONSTRUKSI DI KABUPATEN MANOKWARI (Studi Kasus: PT. Jabez Perkasa) - Anna Margaretha Andreana Malir; Dirarini Sudarwadi; Y. Heri Saptomo (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2018)
In construction project work, constraints usually occur on the project work, both constraints that have already been taken into account and constraints that are beyond the calculation of the planner. These obstacles are the cause of the delay in the completion of the project, so that the project does not take place according to plan. The object of research on the PT. Jabez Perkasa Project Team in Manokwari Regency, West Papua Province by means of distributing questionnaires. Determination of the delay rating at ten (10) factors is based on the acquisition of the highest RI value (Relative Index) and the data analysis technique used to find the most influential subfactor on each factor using Factor Analysis. The results of the study using the Relative Index (RI) that the factors that most influence the delay in the implementation of the building construction project work carried out are material factors with the RI value of 0.876. The most influential subfactors on ten factors of delay based on factor analysis are subfactors of inadequate number of workers, subfactor delays in availability of materials, subfactor damage to equipment, subfactors on surface and subsurface conditions, subfactors for late payment of salaries to employees, subfactors of prolonged rainfall intensity, subfactor changes in working time by the contractor, subfactor changes in the scope of work at the time of implementation, subfactor determination of the duration of work that is not careful, subfactor processes and procedures for evaluating the progress of the old work and through the agreed schedule.